Protein sources diversity from Gunungkidul District, Yogyakarta Province, Indonesia - Eny Palupi; FAISAL ANWAR; IKEU TANZIHA; MADE ALIT GUNAWAN; ALI KHOMSAN; FITRIANINGRUM KURNIAWATI; MUSHLICH MUSLICH (Society for Indonesian Biodiversity, 2020)
Abstract. Palupi E, Anwar F, Tanziha, Gunawan MA, Kurniawati AKF, Muslich M. 2020. Protein sources diversity from Gunungkidul District, Yogyakarta Province, Indonesia. Biodiversitas 21: 799-813. This research aimed to identify forgotten side-dish diversity from food-insecure area, Gunungkidul District, Yogyakarta, Indonesia. A qualitative data were gathered by using Focus Group Discussion followed by in-depth interviews with 24 key persons from Pucung and Mertelu villages, Gunungkidul. Proximate analysis and enzymatic gravimetric fiber analysis were also performed to get the first impression concerning the nutrient quality of the selected sources. As many as six edible insects, five aquatic animals, eight legumes and seeds, five fermented foods, eight mushrooms, three by-products, more than ten protein-rich plants, and five aquatic plants were identified as forgotten indigenous protein source from Gunungkidul, Yogyakarta. All aspects about scientific name, local value, Halal assurance, handling method, processing technique, and serving method of these sources have been presented on this article. Early investigation on the nutrient quality of the identified source reveals that grasshopper, caterpillar, aquatic snail, came out as the highest protein content compared to egg as a standard. Tempe -mlanding and -benguk also could be great alternatives as future plant-based protein sources. This investigation uncovers abundant protein sources diversity potential as future protein sources for supporting future food and nutrition security and sustainability.